Exosomes and non-coding RNAs in the regulation of neuroinflammation after ischemic stroke: mechanisms and therapeutic perspectives - Wei, Dekai; Li, Fujun; Guo, Chunhui; Chen, Jibing; You, Yanqiu (Frontiers in Immunology, 2025)
Ischemic stroke, one of the cerebrovascular diseases with the highest global disability and mortality rates, is characterized by secondary neuroinflammatory injury during its pathological progression, which remains a major challenge in clinical management. Although reperfusion therapies, including intravenous thrombolysis (IVT) and endovascular mechanical thrombectomy (EVT), have significantly improved acute-phase blood flow restoration, the neuroinflammatory cascade triggered post-reperfusion exacerbates neuronal damage. Key mechanisms include microglial overactivation and blood-brain barrier (BBB) disruption, ultimately leading to poor neurological outcomes. Recent studies have increasingly revealed the pivotal roles of exosomes and non-coding RNAs (ncRNAs) in post-ischemic stroke pathology. Specifically, exosomes, as natural nanocarriers, demonstrate targeted regulation of immune-inflammatory cascades in cerebral ischemia/reperfusion injury due to their low immunogenicity and efficient delivery capacity; complementarily, ncRNAs participate in pathophysiological processes including apoptosis, angiogenesis, inflammatory responses, and hypoxic stress through epigenetic regulatory mechanisms. This review systematically deciphers the regulatory networks of exosomes and ncRNAs in post-stroke pathological progression and neural repair, with particular focus on their molecular mechanisms in modulating specific inflammatory components. Building on current advances, we emphasize that while affirming the clinical value of reperfusion therapy, it is imperative to integrate evidence-based secondary prevention systems to address stroke management challenges. Notably, exosome-derived ncRNAs have emerged as promising diagnostic/therapeutic candidates: they not only precisely regulate inflammation-related pathways but also provide a novel strategy for developing targeted delivery systems. With deepening mechanistic understanding, exosome-based therapies are expected to revolutionize therapeutic paradigms for neuroinflammatory disorders, paving new avenues for precise intervention and functional recovery in stroke patients.